2007
DOI: 10.1088/0022-3727/40/11/013
|View full text |Cite
|
Sign up to set email alerts
|

The determination of infrared optical constants of rare earth fluorides by classical Lorentz oscillator model

Abstract: Rare earth fluoride (REF3, RE = La, Ce, Pr, Sm, Er, Yb, Y) films were deposited on Ge(1 1 1) and silicon wafers in order to determine optical constants from the near infrared up to the high frequency tail of the reststrahlen band. The FT-IR transmission spectrum and the reflection spectrum were used to examine the infrared optical properties of the fluorides. The optical constants of the films in the infrared spectrum from 2 to 20 µm were calculated using the classical Lorentz oscillator model by fitting the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The profile of refractive index is in good agreement with the result for depth profiles of Ba and Pr presented in Fig. 6, since BaClF has a greater refractive than that of rareearth fluorides [20,22]. It has been reported that the Gaussian index profile and quintic-index profile are near the optimum profile to minimalize the Fresnel reflections [23], therefore, in our investigation, an extraordinarily lower reflection and effective refractive index can be attributed to an appropriate refractive index gradient existing in the layer.…”
Section: Baclf-prfsupporting
confidence: 87%
See 1 more Smart Citation
“…The profile of refractive index is in good agreement with the result for depth profiles of Ba and Pr presented in Fig. 6, since BaClF has a greater refractive than that of rareearth fluorides [20,22]. It has been reported that the Gaussian index profile and quintic-index profile are near the optimum profile to minimalize the Fresnel reflections [23], therefore, in our investigation, an extraordinarily lower reflection and effective refractive index can be attributed to an appropriate refractive index gradient existing in the layer.…”
Section: Baclf-prfsupporting
confidence: 87%
“…The effective indices of refraction n and extinction coefficient k was derived by using Lorentz oscillator as a dispersion model, as described in details in our previous studies [19,20]. The profile of refractive index was also investigated using OptiChar (version 8.85), which is one of the modules of OptiLayer thin film software (OptiLayer GmbH, Russia) [21].…”
Section: Characterization Of Combinatorial Materials Librariesmentioning
confidence: 99%
“…[6] The most often used techniques have been physical vapor deposition (PVD) methods, e.g., electron beam evaporation (EBE), [4,5,[7][8][9][10] and thermal evaporation. [9,[11][12][13][14][15] Evaporation has also been applied to the fabrication of epitaxial Y x La 1-x F 3 (x ¼ 0-0.8) thin films onto GaAs substrates, [16] as well as YF 3 /ZnS/Ge/ ZnS multilayer structures on germanium substrates. [17] Because the evaporation distribution is not geometrically (and perhaps compositionally) uniform, the properties of the coating can vary spatially over the substrate holder.…”
Section: Introductionmentioning
confidence: 99%
“…Crystal structure of SmF 3 films SmF 3 films have two types of crystal structure according to the deposition temperature, which are Pnma and P3C1. The SmF 3 films deposited in our experiment belong to P3C1 structure according to the far infrared reflective spectrum that is published in the previous work [11]. The SmF 3 films deposited at different temperature from 100 8C to 250 8C are all polycrystalline films, which are shown in Fig.…”
Section: Resultsmentioning
confidence: 97%